Networked Learning Physics of Semiconductors through a Virtual Laboratory Environment - Triantis, D.; Stavrakas, I.; Anastasiadis, C.; Marinos, I. (Proceedings of the International Conference on Networked Learning, 2008)
This poster is part of the Symposium organised by Demosthenes Stamatis and Theodoros Kargidis Virtual laboratory tools have been introduced a long time ago. Such tools have been used into the learning procedure in order to help students to increase their performance through a user friendly tool that stimulates them on their study. Additionally, when the high cost of hardware replacement and maintenance is put in contrast to the flexibility of adding new subjects on a laboratory course the virtual laboratory environment tools render a power tool for educational purposes. Statistics show that students do not spend adequate time preparing for an upcoming laboratory module, thus new methodologies and software have recently been developed and offered to students in order to increase their performance in laboratory modules. In this work a virtual laboratory environment that was built is described, discussed and evaluated. The software deals with the laboratory assignments of Semiconductor Physics. Semiconductor Physics was chosen since it is a first year module that is not connected to any background knowledge the students should be familiar with. The evaluation was made by providing the software to some of the students and comparing their performance with the corresponding performance of the students that had no access to the software. It is concluded that the software tool that was provided to the students before taking the laboratory increased their performance. It was also observed that this tool mainly serves weaker students since, according to the evaluation tests, they are mainly helped to achieve a pass score.